Teacher's field guide : 7 truths about teaching to help you start off strong, avoid burnout, and stay in love with teaching - Hemms, Kerry; White, Graham (New York Morgan James Publishing, 2017)
Teacher's Field Guide is the ultimate burnout prevention and treatment toolkit. It prepares brand new teachers for the reality of the classroom and helps overworked, under appreciated, frustrated veterans regain the sense of purpose and excitement they felt as a new teacher. While most books for teachers are all about curriculum and teaching methods, Teacher's Field Guide is about the "other stuff" that leaves so many teachers feeling drained. It's the true tips, tools, and strategies teachers need to manage not only the classroom, but the real demands of the workload and day to day life of a teacher.
Mindset management. Truth #1 : we begin with a vision -- Classroom management. Truth #2 : if you don't have a plan before the students arrive, they will eat you alive -- Workload management. Truth #3 : you can trade your bag of bricks for a bag of tips -- People management. Truth #4 : all relationships matters -- Stress management. Truth #5 : there will be days when you feel like it's too much -- Self-management. Truth #6 : self-care is not selfish -- Big picture management. Truth #7 : you will have life-changing moments that make it all worth it -- Love the journey : stay encouraged.
105088
Keywords: Teaching; First year teachers; Motivation in education; Conduct of life; Effective teaching